A review and empirical findings of fasciae and muscle interactions in low back pain - van Amstel, Robbert N.; Weide, Guido; Wesselink, Eddo O.; Noten, Karl; Jacobs, Karl; Pool-Goudzwaard, Annelies L.; Jaspers, Richard T. (Frontiers in Physiology, 2025)
BackgroundLow Back Pain (LBP) is a global musculoskeletal disorder affecting quality of life, with 90% of cases categorized as nonspecific, indicating that the underlying cause is unknown. One of the current treatment modalities that physiotherapists use are fascia tissue manipulations (FTMs), such as soft tissue mobilization, myofascial release, and elastic tape, to enhance joint mobility and muscle flexibility in LBP individuals.PurposeThis review and experimental research explore the hypothetical mechanisms of FTMs using Skin Displacement (SKD), either by hand or with elastic tape.MethodsSeveral hypotheses regarding the working mechanisms of FTMs are discussed through inductive reasoning based on literature and new experimental results using ultrasonography and cadaver dissection. In this paper, stiffness is defined as the ratio of the applied force to the resulting strain, based on Hooke’s law. We focus on the role of lumbar fasciae and skeletal muscles, as well as the linkages between skin, fasciae, skeletal muscles, and joints, including the SKD-induced stress transmission between these structures. Furthermore, we discuss how the mechanical properties and stiffness of these structures can be altered.ResultsThe skin connects densely to the fasciae, back muscles, and spine, contributing to the stiffness of structures in the lumbar region. SKD maneuvers transmit stress to deeper tissues, causing strain and displacement of the thoracolumbar fascia, back muscles, and arthrofascia. These deformations may alter the active and passive mechanical properties of deeper tissues including fascia and muscle, by triggering stress-relaxation as well as structural adaptation.ConclusionThis paper provides indications that the skin is strongly connected to the thoracolumbar fascia, back muscles, and spine. These connections are possibly enhanced in patients with LBP. Stress applied to the skin by SKD maneuvers is shown to be transmitted to the underlying anatomical structures via these connections and can alter the stiffness of fasciae and skeletal muscles. The working mechanisms of FTMs potentially alter the quantity and composition of matrix components, as well as the contractile activity of muscle fibers, and traction forces of (myo)fibroblasts and other cells within the matrices. FTM-induced stress and alterations in anatomical structures not only improve joint mobility but also promote regeneration and tissue adaptation via various mechanisms resulting in pain relief.